RECONTEXTUALIZING THE APPOINTMENT PROCEDURES OF CONSTITUTIONAL JUDGES IN MAINTAINING THE INTEGRITY AND PROFESSIONALISM OF THE COURT - Musmulyadi; Hasdinar (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum Universitas Islam Negeri Alauddin Makassar, 2024)
ABSTRACT Judicial power is independent power to carry out law enforcement and justice. Judges are judges who must have broad insight and experience in the field of the constitution so that they will produce various breakthroughs in the context of realizing restorative constitutional justice so that the Constitutional Court becomes a judicial institution that can be trusted and trusted by people to obtain their constitutional rights. The main problem in this research is related to how the legal basis for summoning a candidate for a constitutional court judge is based on the mandate of the Constitution, and how to recontextualize procedural efforts to summon court judges to create judges with integrity and professionalism. The purpose of this research is to see the similarities between calling candidates for constitutional court judges and the procedures for appointing judges contained in the Constitution and other statutory regulations, as well as to contribute theoretical thinking regarding efforts to recontextualize the procedures for appointing court judges in order to produce an institution of judges and justices with integrity. and professionalism. This research was prepared using library research with a normative juridical approach, namely the study of principles and statutory regulations. The results of this research are that the legal basis for appointing constitutional court judges is regulated in the 1945 Constitution at market 24 C paragraph 3 and also in the Constitutional Court law at articles 19 and 20 paragraph 2. Regarding recontextualization efforts in creating judges with integrity and professionalism, then at the stage of selection and appointment of judges, it must involve a panel of experts, and also the Judicial Commission, as well as the process of selecting constitutional court judges by the 3 institutions involved, namely the President of the DPR and the Supreme Court must clarify the selection process, and what is no less important is that in The process of submitting judges to the Constitutional Court must be carried out openly and involve public participation. Keywords: Recontextualization, Appointment of Judges, Integrityy, Proffesionality.